Educational Leadership in the 21st Century: The Relevance of The Among Ki Hajar Dewantara System - Ivan Riyadi; Sri Sumarni (Islam Transformatif : Journal of Islamic Studies, 2025)
This research is relevant to 21st-century educational leadership because it emphasizes education based on love and care. The 21st century demands educators to keep up with developments in science and technology (IPTEK), even though this presents challenges and indifference. Therefore, the among system of Ki Hajar Dewantara needs to be understood in depth, because it emphasizes the role of educators as mentors, motivators, and role models. In accordance with the among system that applies the educational trilogy of Ki Hajar Dewantara ing ngarsa sung tulada, ing madya mangun karsa, tut wuri handayani is considered to be in line with the need to form quality human resources. This research uses a literature study by examining the works of Ki Hajar Dewantara and related scientific literature. It focuses on the principal's understanding of 21st-century characters to strengthen their role in improving the quality of education and human resources in a global era full of competition and demands for expertise.